Civil Liberties and National Security: Judicial Review of Executive Power - Shah, Pinky (2007)
Throughout United States history, national security has often been used as a pretext for abridgements of civil liberties of citizens and foreign nationals. The conventional wisdom is that courts are ineffective as guardians of liberty and the historical record provides clear examples of this deference to the executive during times of war. Nonetheless, individuals rely on the process of judicial review as the forum through which they can assert their rights. The terrorist attacks on September, 11 2001 mobilised the country against fighting terrorism and resulted in the executive amassing considerable detention authority over foreign nationals and citizens whom he unilaterally designated as 'enemy combatants'. As these cases worked their way up the judicial hierarchy to the Supreme Court, they were widely seen as a defeat for the executive's claim of unlimited and unchecked detention authority. This dissertation argues quite the opposite: a close examination of legal and other contemporary documents shows that rather than deviating from the conventional wisdom, the courts conformed considerably. This has clear implications for the rights of citizens and foreign nationals in the current undefined 'war on terrorism' and for expansions of executive power in subsequent 'wars', as it is the precedents that are set during this war that will determine how executives will respond to future crises.